Promoting Agro-Enterprise and Agro-Food Systems Development in Developing and Transition Countries : Towards an Operational Strategy for the World Bank Group - World Bank (Washington, DC, 2013)
This paper sets out a strategic framework for WBG assistance for the modernization of agro-food systems in client countries. The objective of this strategy is to enhance the competitiveness of food, feed, and fiber systems-as a powerful source of growth and income generation-and to do so in a manner in which the poor are major beneficiaries in their capacities as consumers, farmers, workers, and entrepreneurs. This is a major challenge, not only because of the long-standing constraints faced by developing country farmers and agro-enterprises (i.e., weak infrastructure, anti-business policies, etc.) but also because major changes in the global agro-food market are tilted toward those economic agents who have capital, superior organizational and marketing skills, and an acute understanding of consumer requirements. Those lacking such assets and capabilities risk being (further) marginalized. The focus of attention here is on those enterprises, activities, institutions, and relationships that occur off the farm-in other words, those entities and functions that deliver material inputs to the farming sector and transform, distribute and otherwise add value to food and fiber products, yet are not directly engaged in primary production and natural resource management. The shorthand term for this sphere of activity and institutions is agro-enterprise activity. As already demonstrated in a number of countries (including China, Chile, Thailand, Taiwan, Brazil, Mexico and Kenya), agro-enterprise activity-sometimes also referred to as agribusiness can be a powerful source of growth, income diversification and poverty alleviation. However, competitive agro-enterprise activity does not emerge spontaneously. It requires a resourceful, market-oriented private sector which is willing and able to bear commercial and other risks, and a facilitative enabling environment comprising policies, rules, and infrastructure. With consumer demand and agricultural markets undergoing continuous change, sustained agro-enterprise success requires flexibility and the capacities to refine one's approaches, products, and services.